Dual Energy X-Ray Absorptiometry (DEXA) in Evaluation of the Proximal Femur after Repair of Proximal Femoral Physeal Fractures in Immature Dogs - Tillson, D. M.; Roush, J. K.; McLaughlin, R. M., Jr.; Toll, Ph. W.; Richardson, D. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Thin slices of the proximal femora of twelve immature dogs were examined with dual energy x-ray absorptiometry, after surgical creation and repair of proximal femoral physeal fractures. A protocol for the subtraction of microvascular barium sulphate was used to eliminate interference from the barium with the determination of bone mineral content (BMC), bone mineral density (BMD) and volumetric bone mineral density (VBMD). The results showed there was a significant decrease in the BMC (four and eight weeks) and BMD (eight weeks) for the entire proximal femora of the operated side when compared to the non-operated side. Significant decreases were also seen for the BMC of the physeal region at week eight and the VBMD of the metaphyseal area in the two week femora. The findings with DEXA support the clinical findings of femoral neck thinning in proximal femoral physeal fractures that are surgically repaired. The DEXA findings suggest that the quality of the bone of the femoral neck is less as shown by the decreased BMC, BMD and VBMD. Postoperative complications may occur at a higher frequency when such quality changes occur.Dog proximal femora were examined with DEXA after surgical creation and repair of proximal femoral physeal fractures. DEXA findings support clinical findings of femoral neck thining after fracture repair.
Keywords: DEXA; bone densitometry; microangiography; proximal femur fracture